Trapping ultracold atoms in a time-averaged adiabatic potential - Gildemeister, M; Nugent, E; Sherlock, B; Kubasik, M; Sheard, B; Foot, C (2010)
We report an experimental realization of ultracold atoms confined in a time-averaged, adiabatic potential (TAAP). This trapping technique involves using a slowly oscillating (∼kHz) bias field to time-average the instantaneous potential given by dressing a bare magnetic potential with a high-frequency (~MHz) magnetic field. The resultant potentials provide a convenient route to a variety of trapping geometries with tunable parameters. We demonstrate the TAAP trap in a standard time-averaged orbiting potential trap with additional Helmholtz coils for the introduction of the radio frequency dressing field. We have evaporatively cooled 5×104 atoms of Rb87 to quantum degeneracy and observed condensate lifetimes of longer than 3 s. © 2010 The American Physical Society.